Implementasi Teknik Pengambilan Gambar pada Produksi Video Dokumenter “Bisakah Aku Kembali?” - Siti Arifa Rosa; Anggita Nuringtyas; Encang Saepudin; FX. Ari Agung Prastowo (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2026)
The Director of Photography (DOP) is responsible for the visual aspects of documentary video production, covering the pre-production, production, and post-production stages. The DOP plays a crucial role in translating concepts and messages into visual form through the arrangement of composition, lighting, camera angles, and camera movement to produce visuals that are both aesthetically appealing and meaningful. The purpose of this final project report is to explain the role of the DOP in the production process of a documentary video that focuses on the rehabilitation of the Javan slow loris. The method used is a descriptive approach to systematically and comprehensively identify the object of study. In the pre-production stage, the DOP designs the visual concept, prepares the shot list, creates the storyboard, and coordinates with the director. During the production stage, the DOP is responsible for capturing footage by applying cinematographic techniques. In the post-production stage, the DOP conducts visual evaluation and provides input during the editing process. In conclusion, the Director of Photography has effectively fulfilled their role in producing visual quality that supports message delivery in the documentary Bisakah Aku Kembali? about Javan slow loris rehabilitation.